Electrolyte disturbances and cardiac failure with hypomagnesaemia in anorexia nervosa. Issue 6510 (14th December 1985) - Fonseca, V; Havard, C W
Abstract : A 32 year old woman with anorexia nervosa was admitted to hospital with severe hypocalcaemia and hypokalaemia that was refractory to replacement treatment but that responded immediately to an infusion of magnesium. She also had congestive cardiac failure that responded to magnesium replacement. The mild hypomagnesaemia found in this patient was responsible for the refractory hypocalcaemia. Minor deficiencies of magnesium may cause severe hypocalcaemia and hypokalaemia that are refractory to replacement treatment. Prompt replacement of magnesium may prevent prolonged tetany, cardiac arrhythmias, and heart failure.